1976
DOI: 10.1017/s000335610003542x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between live weight, age and dry-matter intake for beef cattle after different levels of food restriction

Abstract: SummaryFive groups of 24 Aberdeen Angus steers, initially 8 months old and 185 kg in weight were subjected to varying degrees of restriction of energy intake, by feeding them on diets containing 1·45 to 2·85 Meal metabolizable energy (ME)/kg dry matter (DM) for 16 weeks. During the realimentation period that followed, all animals were fed ad libitum on the diet containing 2·85 Meal ME/kg DM. When realimentation began the feed consumption of all animals, which had been markedly different, rapidly became similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The phenomenon of animals showing enhanced performance after periods of nutritional restriction has been known for many years and has been comprehensively reviewed (Wilson and Osbourn, 1960;Allden, 1970;O'Donovan, 1984). Several explanations have been proposed as to the cause of this compensation including reduced maintenance requirements (Saubidet and Verde, 1976), alterations of the composition of tissue gains (Thompson, Bickel and Schiirch, 1982;Baker, Young and Laws, 1985) and increased food intake (Meyer, Hull, Weitkamp and Bonilla, 1965). In the present experiments, a reduction in winter food level led to increased herbage intake at pasture and increased live-weight gains.…”
Section: Discussionsupporting
confidence: 45%
“…The phenomenon of animals showing enhanced performance after periods of nutritional restriction has been known for many years and has been comprehensively reviewed (Wilson and Osbourn, 1960;Allden, 1970;O'Donovan, 1984). Several explanations have been proposed as to the cause of this compensation including reduced maintenance requirements (Saubidet and Verde, 1976), alterations of the composition of tissue gains (Thompson, Bickel and Schiirch, 1982;Baker, Young and Laws, 1985) and increased food intake (Meyer, Hull, Weitkamp and Bonilla, 1965). In the present experiments, a reduction in winter food level led to increased herbage intake at pasture and increased live-weight gains.…”
Section: Discussionsupporting
confidence: 45%
“…Saubidet and Verde (1976), in an experiment with steers. found that the greater the severity of feed restriction, the higher the realimentation feed intake at equal weight.…”
Section: Allometrymentioning
confidence: 99%
“…(1991) in Brahman cattle and beef heifers, respectively. Saubidet and Verde (1976) in an experiment with steers,…”
Section: Resultsmentioning
confidence: 99%